Femme Theory: Refocusing the Intersectional Lens - Hoskin, Rhea Ashley (Atlantis, 2017)
This paper seeks to develop a theory of subversive femininities or femme theory. It argues for the inclusion of femmephobia in intersectional analyses and provides the theoretical groundwork necessary for feminist theorists and researchers to incorporate an analysis of femmephobia into their studies of oppression.